Food, medicine, and the quest for good health nutrition, medicine, and culture - Chen, Nancy N. (Columbia University Press, 2008)
Drawing on Medical Texts and food therapy practices from around the world and throughout history, Nancy N. Chen locates old and new crossovers between food and medicine in different social and cultural contexts. The consumption of spices, sugar, and salt was once linked to specific healing properties, and trade in these commodities transformed not just the political economy of Europe, Asia, and the New World but local tastes and food practices as well. Today's technologies are rapidly changing traditional attitudes toward food, enabling the cultivation of new admixtures, such as nutraceuticals and genetically modified food, that link food to medicine in novel ways. Chen considers these developments against the evolving food regimes of the diet industry in order to build a framework for understanding diet as individual practice, social prescription, and political formation